Efektivitas Intervensi Berbasis Komunitas untuk Trauma Kompleks Anak-anak Gaza : Suatu Analisis Protocol-Based Treatment - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
This meta-analysis evaluates the effectiveness of community-based interventions in addressing complex trauma among children in Gaza through a systematic analysis of 42 studies (N=4,873) published between 2010 and 2024. The findings reveal a significant treatment effect (g=0.78, 95% CI [0.65, 0.91], p<.001) with moderate heterogeneity (I²=68%). School-based interventions demonstrate the greatest effect (g=0.89), followed by family interventions (g=0.76) and peer-group interventions (g=0.65). Furthermore, protocol-based treatment significantly reduces PTSD symptoms (42.3%), anxiety (38.7%), and depression (35.2%) among children in Gaza. Moderator analysis identifies intervention duration (β=0.34, p<.01) and family involvement (β=0.29, p<.01) as significant predictors of successful treatment outcomes for complex trauma. Lastly, meta-regression results indicate a linear relationship between intervention intensity and symptom improvement (R²=0.45, p<.001). These findings expand on previous research by Thompson et al. (2021) and Al-Krenawi (2022) by identifying specific effective intervention components within the Gaza context. Additionally, the discovery that a phased approach integrating community support with protocol-based treatment yields optimal outcomes presents a novel contribution not previously addressed in meta-analyses.